ERRATUM - Editorial , Editorial Office (Acta Biomedica Atenei Parmensis, 2022)
ERRATUM Gallo M, Street ME, Guerra F, Fanos V, Marcialis MA. A review of current knowledge on Pollution, Cigarette Smoking and COVID-19 diffusion and their relationship with inflammation: Inflammation, pollution and Covid-19. Acta Biomed [Internet]. 2020 Oct. 21 [cited 2022 May 6];91(4):e2020148. Available from: https://www.mattioli1885journals.com/index.php/actabiomedica/article/view/10263 The above-cited article included a figure (Figure n.2) that was adapted without indicating the original source of Olds JL, Kabbani N. Is nicotine exposure linked to cardiopulmonary vulnerability to COVID-19 in the general population? FEBS J. 2020; 287 (17): 3651-3655. The authors apologize for this unpleasant inconvenience The online version of the article has been updated with the correct original source and the license permission from the FEBS J. Editors to publish the above-cited Figure (https://doi.org/10.23750/abm.v91i4.10263 ).